Instructional Risk and Crisis Communication at Higher Education Institutions during COVID-19: Insights from Practitioners in the Global South and North - Andreas Schwarz; Deanna D. Sellnow; Timothy D. Sellnow; Lakelyn E. Taylor (Journal of International Crisis and Risk Communication Research, 2024)
During the COVID-19 pandemic, challenges at higher education institutions (HEIs) in managing public health crises were revealed globally. The literature on HEIs has focused on Western/Northern countries and lacks theoretically grounded studies of internal instructional risk communication. This article reports the results of interviews with HEI communication practitioners at 28 universities in 16 countries in the Global South and North regarding their practices of message design and distribution during COVID-19. Using the IDEA model of instructional risk communication, the results revealed that practitioners’ communication emphasized action and dissemination over internalization and explanation. Practitioners from the Global South were more likely to perceive personal relevance as important and integrate it into their messages than those from the Global North. Practitioners from the Global South also used credible sources and translated technical jargon for lay audiences more often than those in the Global North. Most of the practitioners’ risk messaging was informed by personal experience and intuition rather than by theory or best practice models.